Interpretasi Makna Hati dan Visi Pemulihan dalam Yehezkiel 36: 26-28 Menurut Perspektif Spiritualitas Kongregasi Imam-Imam Hati Kudus Yesus - Leo Agung Tyas Prasaja (Fakultas Teologi, Universitas Sanata Dharma, 2025)
This article discusses the interpretation of the meaning of heart in the book of Ezekiel 36: 26-38 from the perspective of the spirituality of the Congregation of Priests of the Sacred Heart of Jesus. This research is motivated by the use of the text of Ezekiel 36: 26-38 as a devotional reading material in a congregational order of worship which is indicated to have similar meaning with the spirituality of the congregation. By exploring textually from the Book of Ezekiel and the principles of congregational spirituality, this article aims to show how the meaning of heart in Ezekiel 36:26-28 can be interpreted from the perspective of the spirituality of the Congregation of Priests of the Sacred Heart of Jesus by describing the interpretation of the meaning of heart in the Book of Ezekiel 36: 26-38 and the spirituality of the congregation as well as looking deeper into the similarities and differences in the meaning of heart in both. The author uses descriptive-analytical method with qualitative approach in this research. There are 3 important questions that become the instruments of this research, namely: What is the context of the Book of Ezekiel 36: 26-28? What is the spirituality of the heart in the Congregation of Priests of the Sacred Heart of Jesus? What are the similarities and peculiarities of each in interpreting the meaning of heart? The results of the research show that there is a new understanding and meaning of the interpretation of the meaning of the heart towards Ezekiel 36:26 from the perspective of the spirituality of the Congregation.AbstrakArtikel ini membahas mengenai interpretasi makna hati dalam kitab Yehezkiel 36: 26-38 dari sudut pandang spiritualitas Kongregasi Imam-imam Hati Kudus Yesus. Penelitian ini dilatarbelakangi oleh adanya penggunaan teks Kitab Yehezkiel 36: 26-38 ini sebagai bahan bacaan permenungan dalam sebuah tata peribadatan kongregasi yang disinyalir memiliki kesamaan pemaknaan dengan spiritualitas kongregasi. Dengan menggali secara tekstual dari Kitab Yehezkiel dan prinsip-prinsip spiritualitas kongregasi, penelitian ini bertujuan untuk memperlihatkan bagaimana makna hati dalam Yehezkiel 36:26-28 dapat diinterpretasikan dari perspektif spiritualitas Kongregasi Imam-Imam Hati Kudus Yesus dengan mendeskripsikan interpretasi makna hati dalam Kitab Yehezkiel 36: 26-38 dan spiritualitas kongregasi serta melihat lebih dalam kesamaan dan perbedaan makna hati dalam keduanya. Penulis menggunakan metode deskriptif-analitis dengan pendekatan kualitatif dalam penelitian ini. Adapun 3 pertanyaan penting yang menjadi instrumen penelitian ini, yaitu: bagaimana konteks Kitab Yehezkiel 36: 26-28? Apa spiritualitas hati dalam Kongregasi Imam-imam Hati Kudus Yesus? Apa kesamaan dan kekhasan masing-masing dalam menginterpretasi makna hati? Hasil penelitian menunjukkan bahwa adanya pemahaman dan pemaknaan baru mengenai interpretasi makna hati terhadap Yehezkiel 36:26 dari perspektif spiritualitas Kongregasi yang menyirat pesan pada dimensi pemulihan dan penebusan umat manusia yang senada.